The Utilization of HR Analytics in Optimizing Human Resource Management: A Case Study on Astra Motor Makassar - Nasir, Nasir nasir (Indonesian Journal Of Economy Studies, 2025)
This study aims to explore the application of HR Analytics in human resource management at Astra Motor Makassar. The background of this research is based on the need to improve operational efficiency and more data-driven decision-making in human resource management. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that HR Analytics has been successfully implemented at Astra Motor Makassar, which contributes to more effective HR management. This technology helps in more structured data integration, predicts HR trends such as training needs and possible turnover, and improves the company's operational efficiency. While it provides significant benefits, challenges such as employee readiness and understanding of data analytics still need to be addressed through more in-depth training. The conclusion of this study shows that Astra Motor Makassar has great potential to optimize human resource management through HR Analytics with a more inclusive and sustainable strategy.